FAKTOR YANG MEMPENGARUHI MINAT PEMUDA TANI TERHADAP PROFESI PERTANIAN DAN DAMPAKNYA TERHADAP PRODUKTIVITAS USAHATANI DAN CURAHAN KERJA - Suryana, Yayan; Dasipah, Euis; Nataliningsih, Nataliningsih (Papanda Publisher, 2024)
This study aims to determine the faktors that influence the interest of young farmers in the agricultural profession and their impact on work output and farming productivity. The unit of analysis is the youth farmer in Warungkondang sub-district, Cianjur. The technique of determining the respondents was carried out by sampling using a simple random technique, the sample size using the Slovin formula obtained 60 units. The analysis technique for testing the hypothesis used multiple linear regression analysis and chi square. The results of the study obtained that the interest of young farmers in the agricultural profession in Warungkondang District, Cianjur Regency consisted of dimensions: attention; feeling; satisfaction; hope; and experience obtained achievement level of 48.83% sufficient criterion. Faktors that influence the interest of young farmers in the agricultural profession in Warungkondang District, Cianjur Regency are: Land tenure; Knowledge and insight; Experience ; Farming income; business certainty; Stimulant from the government; and modernization of technology obtained an achievement level of 46.01% sufficient criterion. The interest of young farmers in the agricultural profession is simultaneously influenced by the following faktors: farm income; business certainty; Stimulant from the government; and Technology modernization. Partially the faktors that have no significant effect are: Business certainty. The interest of young farmers in the agricultural profession has an impact on work output. The outpouring of youth farming work that contributed to paddy rice farming activities was 48 HKP out of 105 HKP or 45.98% sufficient kriteria. The interest of young farmers in the agricultural profession has an impact on farming productivity. Farming productivity achievement level of 6.103 ton/ha sufficient kriteria.